Construction method of coal gangue filling roadbed water stable layer
By adding straw fibers and gelling materials to the roadbed water stability layer of the coal gangue filler to form a specific proportion of mixture, the problems of high environmental resource pressure and reflective cracks in the traditional roadbed water stability layer are solved, and the crack resistance of the roadbed is improved and load-bearing capacity is enhanced.
Patent Information
- Application Number
- CN202411622377.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
The use of sand and gravel and other aggregates in the water-stabilizing layer mixture of traditional road subgrades has problems such as high environmental resource pressure and high cost, and the coal gangue subgrade is prone to reflective cracks, affecting the load-bearing capacity.
The coal gangue filler roadbed water stabilization layer construction method is adopted. By mixing coal gangue aggregate, gelling material, straw fiber and alkali exciter in a specific proportion, a mixture with a moisture content of 8.8% to 9.7% is formed, and the mixture is spread through the paving. The machine and the roller are constructed to form a roadbed with excellent crack resistance.
It effectively improves the crack resistance of coal gangue base mixture, improves the bearing capacity and stability of the roadbed, and reduces environmental resource pressure and cost.
Smart Images

Figure CN119462047A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water-stabilizing layer construction, and in particular to a method for constructing a water-stabilizing layer of a gangue-filled roadbed. Background Art
[0002] Water-stabilizing layer is the abbreviation of cement-stabilized gravel layer, which is to use cement to consolidate graded gravel, and complete it through compaction and maintenance. The traditional road subgrade water-stabilizing layer mixture uses sand and gravel as aggregates, and lime, cement, etc. as activators, but there are problems such as great environmental resource pressure and high cost. With the comprehensive utilization of bulk industrial solid waste as an important part of my country's construction of a green, low-carbon circular economic system, it is imperative to use solid waste materials such as coal gangue.
[0003] Coal gangue is one of the mining wastes with the largest stockpile at present. Due to the large crushing value and water absorption rate of coal gangue, and taking into full consideration the seasonal freeze-thaw characteristics in the Northeast region and the physical, chemical and engineering properties of coal gangue, the roadbed paved with coal gangue is prone to reflective cracks, which affects the bearing capacity of the roadbed.
[0004] To this end, the present invention provides a method for constructing a water-stabilizing layer of a gangue-filled roadbed, which solves the above-mentioned technical problems by improving the gangue base mixture. Summary of the invention
[0005] The purpose of the present invention is to provide a method for constructing a water-stabilizing layer of a roadbed filled with coal gangue to solve the problems existing in the above-mentioned prior art.
[0006] To achieve the above object, the present invention provides a gangue-filled roadbed water-stabilizing layer, comprising gangue aggregate, cementitious material, straw fiber and alkali activator;
[0007] The particle size of the coal gangue aggregate is 0.075 mm to 19 mm;
[0008] The cementitious material comprises cement, slag, fly ash and gypsum, wherein the mass ratio of cement, slag, fly ash and gypsum is 55:35:5:5; the dosage of the cementitious material is 4% to 5.5%;
[0009] The amount of the alkali activator is 4% of the slag mass;
[0010] The amount of the rice straw fiber is 1% to 4%, and the length of the rice straw fiber is 4 mm to 12 mm;
[0011] The moisture content of the coal gangue aggregate, the cementitious material, the straw fiber and the alkali activator after mixing is 8.8% to 9.7%.
[0012] Preferably, the gangue aggregate is sieved with standard sieves of 19 mm, 9 mm, 4.75 mm, 2.36 mm, 0.6 mm, and 0.075 mm, respectively.
[0013] Preferably, the gangue aggregate further comprises natural crushed stone, and the natural crushed stone accounts for 30% of the total amount of the gangue aggregate of 0 to 5 mm.
[0014] Preferably, the straw fiber is rice straw.
[0015] Preferably, the rice straw has no rot or mildew on the surface and has good color.
[0016] Preferably, the rice straw is soaked in a 5% by mass NaOH solution for 12 hours, and then washed and air-dried.
[0017] Preferably, the amount of the gelling material is 5.5%.
[0018] Preferably, the blending amount of the rice straw fiber is 3%.
[0019] Preferably, the length of the rice straw fiber is 8 mm.
[0020] A method for constructing a water-stable layer of a gangue-filled roadbed comprises the following steps:
[0021] Construction preparation, preparation of construction raw materials and construction equipment;
[0022] Raw material inspection: inspect the raw materials;
[0023] Mix ratio selection;
[0024] Mixing of mixed materials;
[0025] The water content and cement dosage of the mixed material are tested. If the cement dosage test fails or the water content fails, the mixture mixing step is returned;
[0026] Transportation of mixed materials: transporting the qualified mixed materials to the construction site and making test pieces;
[0027] Use a paver to level and pave the ground, and keep the travel speed of the paver within 1.5m / min;
[0028] Use a roller for static compaction, and control the roller's travel speed at 1.5-1.7 km / h;
[0029] Elevation and flatness inspection. If the inspection fails, manual repair will be performed;
[0030] The roller is used for shaping and vibrating. The speed of the roller is controlled at 1.8-2.5 km / h. The roller is rolled until there is no wheel mark. The roller overlaps 1 / 2 wheel width when rolling.
[0031] Compactness test: if the test fails, the process returns to the roller forming and vibration step;
[0032] Health preservation and finished product protection.
[0033] Compared with the prior art, the present invention has the following advantages and technical effects:
[0034] The method for constructing a water-stabilizing layer of a gangue-filled roadbed provided by the present invention incorporates rice straw fibers. When the mixture is subjected to stress, the rice straw fibers can work together with the base mixture to generate a mechanical bite force, and exert the transfer effect of the rice straw fibers in the interface, so that the force applied to the internal structure of the base mixture is transferred to other structures through the rice straw fibers, thereby playing a bridge role in the internal structure. At the same time, the rice straw fibers are freely dispersed in the base mixture to form a spatial network structure, thereby effectively improving the crack resistance of the gangue base mixture. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 The figure is a comparison of the appearance of the rice straw before and after alkali treatment modification of the present invention;
[0037] Figure 2 is the coal gangue screening distribution curve of the present invention;
[0038] Figure 3 The performance index comparison of the coal gangue of the present invention is shown below;
[0039] Figure 4 It is the 7d unconfined compressive strength of the base mixture of the present invention;
[0040] Figure 5 It is the unconfined compressive strength of the base mixture under freeze-thaw cycle of the present invention for 28 days;
[0041] Figure 6 It is the 28d flexural limit failure load of the bending-tension type load base mixture of the present invention;
[0042] Figure 7 It is the 28d flexural limit failure load of the composite load-bearing base mixture of the present invention. DETAILED DESCRIPTION
[0043] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The described embodiments are only some embodiments of the present invention, not all embodiments. All other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The present invention will be described in detail below with reference to the drawings and in combination with the embodiments.
[0044] The present invention provides a gangue-filled roadbed water-stabilizing layer, comprising gangue aggregate, cementitious material, straw fiber and alkali activator;
[0045] The particle size of coal gangue aggregate is 0.075mm~19mm;
[0046] The cementitious material includes cement, slag, fly ash and gypsum, wherein the mass ratio of cement, slag, fly ash and gypsum is 55:35:5:5; the amount of cementitious material is 4% to 5.5%;
[0047] The dosage of alkali activator is 4% of the slag mass;
[0048] The amount of rice straw fiber is 1% to 4%, and the length of rice straw fiber is 4mm to 12mm;
[0049] The moisture content of the mixture of coal gangue aggregate, cementitious material, straw fiber and alkali activator is 8.8% to 9.7%.
[0050] The present invention incorporates rice straw fibers. When the mixture is subjected to stress, the rice straw fibers can work together with the base mixture to generate mechanical bite force, and exert the transfer effect of the rice straw fibers in the interface, so that the force applied to the internal structure of the base mixture is transferred to other structures through the rice straw fibers, thereby playing a bridge role in the internal structure. At the same time, the rice straw fibers are freely dispersed in the base mixture to form a spatial network structure, thereby effectively improving the crack resistance of the coal gangue base mixture.
[0051] To further optimize the solution, rice straw is used as the straw fiber.
[0052] The plan was further optimized, and the rice straw had no rot or mildew on the surface and had good color.
[0053] To further optimize the solution, rice straw was soaked in 5% NaOH solution for 12 h, then washed and air-dried. Figure 1 Comparison of the appearance of rice straw before and after alkali treatment modification.
[0054] To further optimize the scheme, the gangue aggregate was sieved with standard sieves of 19 mm, 9 mm, 4.75 mm, 2.36 mm, 0.6 mm, and 0.075 mm respectively.
[0055] According to a further optimization scheme, the gangue aggregate also includes natural crushed stone, which accounts for 30% of the total amount of the gangue aggregate of 0 to 5 mm.
[0056] According to the further optimization scheme, the dosage of cementitious material is 5.5%.
[0057] The solution was further optimized, with the addition amount of straw fiber being 3%.
[0058] The solution was further optimized, and the length of the straw fiber was 8 mm.
[0059] Example
[0060] The gangue aggregate of the present invention is sieved with standard sieves of 19 mm, 9 mm, 4.75 mm, 2.36 mm, 0.6 mm and 0.075 mm respectively. The aggregate gradation design of the gangue is as follows: Figure 2 As shown, 30% of the 0-5 mm coal gangue aggregate is replaced by natural crushed stone. Considering that the crushing value and water absorption rate of coal gangue are large, and the water absorption rate of coal gangue is correlated with the particle size, the smaller the coal gangue particle size, the larger its specific surface area, the larger the area in contact with water, and the greater the water absorption rate. In order to reduce the crushing value and water absorption rate of the mixture, as shown in Figure 3 As shown in the figure, the performance indexes of coal gangue are compared. Before replacement, the water absorption rate of coal gangue is 4.26 and the crushing value is 26.8. By replacing 30% of 0-5 mm coal gangue aggregate with natural crushed stone, the water absorption rate and crushing value of coal gangue performance index are reduced to 3.25 and 24.5 respectively, thereby reducing the water absorption rate and crushing value of coal gangue.
[0061] The alkali activator is prepared by using water glass solution using solid water glass with a modulus of 1.3. The chemical compositions of slag, fly ash, cement and coal gangue are shown in Table 1.
[0062] Table 1 Chemical composition of raw materials
[0063]
[0064] The physical indicators of coal gangue were measured, and the results are shown in Table 2.
[0065] Table 2 Performance index of coal gangue aggregate
[0066]
[0067] According to the compaction test method of inorganic binder stabilized materials in JTG E51-2009 "Testing Procedures for Inorganic Binder Stabilized Materials for Highway Engineering", compaction tests were carried out, and the cementitious material dosage was selected to be 4%, 4.5%, 5%, and 5.5%, and the optimal moisture content and maximum dry density were measured. Cylindrical specimens with a compaction degree of 98% and a size of φ150×150mm were prepared, placed in a standard curing environment (20℃, 98% humidity) and cured to the specified age, and the 7d unconfined compressive strength was tested respectively.
[0068] The compaction test shows that the optimum moisture content and maximum dry density of coal gangue mixture under different cementitious material dosages are shown in Table 3.
[0069] Table 3 Compaction test results
[0070]
[0071] As shown in Table 3, with the increase of cementitious material content, the optimum moisture content and maximum dry density of coal gangue mixture gradually increase. This shows that due to the increase of cementitious material, the water demand of coal gangue mixture increases, so the optimum moisture content increases. As the cementitious material fills into the gaps of the dense skeleton of coal gangue mixture, the skeleton of the mixture becomes tighter and the maximum dry density increases.
[0072] The unconfined compressive strength test of the pavement base mixture specimens was carried out under standard conditions with the optimal gradation of coal gangue mixture as the standard and different cementitious material contents added. The results are as follows: Figure 4 shown.
[0073] As the amount of cementitious material increases, SiO2 and Al2O3 in the gangue react with the cement hydration product Ca(OH) and slag powder to produce volcanic ash reaction, and the calcium silicate gelling material produced fills the cracks in the aggregate itself and the gaps between the aggregates, making the gangue mixture more compact. Therefore, the 7d unconfined compressive strength of the specimen shows an increasing trend. When the cementitious material content is 4%, 4.5%, 5%, and 5.5%, the 7d compressive strength is 4.23MPa, 4.48MPa, 4.96MPa, and 5.09MPa, respectively, all of which meet the requirements of the specification. When the cementitious material content increases from 4% to 4.5%, the compressive strength increases slightly, because the aggregate accounts for a large proportion and the aggregate has a large water absorption rate. The increase of a small amount of cementitious material cannot accelerate the setting time of the mixture and fully exert the hardening strength of the cementitious material. When the cementitious material content increases from 4.5% to 5% and 5.5%, the increase in the cementitious material content speeds up the setting time and increases the degree of hardening by 10.7% and 13.6% respectively.
[0074] Since the road is in a seasonally frozen area, the frost resistance of the pavement base material should meet the requirements. A fully automatic low-temperature freeze-thaw tester is used for freeze-thaw cycle test. The test machine freezes for 16 hours, the freezing temperature is -18°C, and then it is immersed in 20°C water for 8 hours to melt. The test piece is taken out, wiped dry, and measured, and the weight is weighed, which means that a freeze-thaw cycle has ended. Freeze-thaw 10 cycles, the standard curing age is 28 days, and the residual compressive strength test is carried out after reaching the number of freeze-thaw cycles. Figure 5 The graph shows the changes of specimens with cementitious material content of 4%, 4.5%, 5%, and 5.5% after 28 days of curing and 10 freeze-thaw cycles.
[0075] After 10 freeze-thaw cycles, the compressive strength of the specimens with different cementitious material content decreased. The strength of the indoor specimens with cementitious material content of 4%, 4.5%, 5%, and 5.5% decreased by 21.8%, 19.8%, 17.4%, and 15.8%, respectively. Because the internal expansion of the specimens caused by the frost heave cycle caused the fine aggregate of coal gangue to peel off and the coarse aggregate to be exposed, the specimens became loose as a whole, resulting in a decrease in compressive strength. The results are shown in Table 4.
[0076] Table 4 BDR index under different cementitious material dosage
[0077]
[0078] It can be seen from Table 4 that after 10 freeze-thaw cycles, with the increase of the cementitious material content, the residual compressive strength ratio BDR also increases as shown in Table 5, and all meet the standard of BDR ≥ 70 in severe seasonal freezing areas.
[0079] The 28d base mixture specimens with different straw fiber content and different straw fiber length were subjected to the flexural limit failure load test (the crack extended to 4cm). The average value of each group of 2 specimens was taken. The final results are as follows: Figure 6 , Figure 7 shown.
[0080] Depend on Figure 6 , Figure 7It can be seen that for the base mixture specimens with and without straw fiber, the composite failure eccentric load is basically larger than the bending-tension failure positive load, and the minimum composite failure load is basically larger than the maximum bending-tension failure load. With the increase of the addition amount of 4, 8, and 12 mm straw fiber, the base mixture shows a trend of first decreasing, then increasing, and then decreasing. At the same straw fiber content, the ultimate failure load strength of the mixture with 8 mm straw fiber is always higher than that of 4 mm and 12 mm straw fiber. When the 4, 8, and 12 mm straw fibers are mixed at a dosage of 1%, the effect of 12 mm straw fiber on the ultimate failure load strength of the mixture is lower than that of 4 mm straw fiber, because the mixing density of 4 mm straw fiber is higher than that of 12 mm straw fiber, but the straw fiber cannot be evenly distributed in the mixture, resulting in more voids and weak stress areas inside the base mixture, and more small weak stress areas are connected to form large weak stress areas, which have an impact on the ultimate failure load that exceeds the effect of straw fiber itself on the toughness of the mixture. Therefore, the ultimate failure load of the 4 mm base mixture is the lowest. At a straw mixing dosage of 2%, the ultimate failure load of 4 mm straw fiber is higher than that of 12 mm straw fiber. Due to the increase in the mixing density of 4 mm straw fiber and the relatively uniform dispersion, the toughening effect of straw fiber is obvious, so the ultimate failure load of the mixture is higher than that of 12 mm straw fiber. When the straw fiber content is 3%, the ultimate failure load of the 8mm straw fiber exceeds the load without straw fiber, which is the highest. When the straw fiber content is 4%, the ultimate failure load of the 4, 8, and 12mm base mixture specimens is significantly reduced, because the addition of more straw fiber reduces the contact area between the aggregate and the cementitious material of the base mixture, and the straw fiber increases the internal voids of the mixture.
[0081] Considering the ultimate failure load strength, after adding straw fiber, the ultimate failure load size has not only been significantly improved, but also indirectly shows that the addition of straw fiber has a certain improvement in the crack resistance of the base mixture. Regardless of the straw length of 4mm, 8mm or 12mm, the load strength reaches the highest point when the straw fiber is added at 3%, so the optimal addition of straw fiber is 3%. At different straw fiber additions, the load strength of 8mm straw is always higher than that of 4mm and 12mm straw, indicating that the optimal addition length of straw fiber is 8mm.
[0082] In summary, when the cementitious material content is 5.5%, the mechanical properties of the coal gangue base mixture are the best, and its 7d unconfined compressive strength can reach 5.09MPa, meeting the requirements of the highway base strength specification. When the cementitious material content of the pavement base material is 5.5%, after 10 freeze-thaw cycles, its 28d unconfined compressive strength can still reach 5.28MPa, showing good anti-freeze performance.
[0083] With the increase of straw fiber content, the ultimate failure load of the gangue base mixture increases first and then decreases. The addition of straw fiber can effectively improve the crack resistance of the gangue base mixture. When the straw fiber content is 3%, its distribution inside the base mixture is relatively uniform, and the anti-cracking performance is the best. When the straw fiber content is greater than 3%, the fibers tend to aggregate into agglomerates to form weak strength areas, which are weak links in the mixture where cracks are prone to occur. When the straw fiber content is less than 3%, the fiber distribution is relatively dispersed, and the crack resistance of the single-filament straw fiber is much lower than the force during the cracking process, resulting in the phenomenon of the straw fiber breaking. Therefore, when the straw fiber length is 8mm and the content is 3%, the anti-reflective crack performance of the gangue base mixture reaches the highest.
[0084] A method for constructing a water-stable layer of a gangue-filled roadbed comprises the following steps:
[0085] Construction preparation, preparation of construction raw materials and construction equipment;
[0086] Raw material inspection: inspect the raw materials;
[0087] Mix ratio selection;
[0088] Mixing of mixed materials;
[0089] The water content and cement dosage of the mixed material are tested. If the cement dosage test fails or the water content fails, the mixture mixing step is returned;
[0090] Transportation of mixed materials: transporting the qualified mixed materials to the construction site and making test pieces;
[0091] Use a paver to level and pave the ground, and keep the travel speed of the paver within 1.5m / min;
[0092] Use a roller for static compaction, and control the roller's travel speed at 1.5-1.7 km / h;
[0093] Elevation and flatness inspection. If the inspection fails, manual repair will be performed;
[0094] The roller is used for shaping and vibrating. The speed of the roller is controlled at 1.8-2.5 km / h. The roller is rolled until there is no wheel mark. The roller overlaps 1 / 2 wheel width when rolling.
[0095] Compactness test: if the test fails, the process returns to the roller forming and vibration step;
[0096] Health preservation and finished product protection.
[0097] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A coal gangue filled roadbed water-stable layer, characterized in that: It includes coal gangue aggregate, cementitious material, straw fiber and alkali activator; The particle size of the coal gangue aggregate is 0.075 mm to 19 mm; The cementitious material comprises cement, slag, fly ash and gypsum, wherein the mass ratio of cement, slag, fly ash and gypsum is 55:35:5:5; the dosage of the cementitious material is 4% to 5.5%; The amount of the alkali activator is 4% of the slag mass; The amount of the rice straw fiber is 1% to 4%, and the length of the rice straw fiber is 4 mm to 12 mm; The moisture content of the coal gangue aggregate, the cementitious material, the straw fiber and the alkali activator after mixing is 8.8% to 9.7%.
2. The coal gangue filled roadbed water-stabilizing layer according to claim 1, characterized in that: The gangue aggregate was sieved with standard sieves of 19 mm, 9 mm, 4.75 mm, 2.36 mm, 0.6 mm and 0.075 mm respectively.
3. The coal gangue filled roadbed water-stabilizing layer according to claim 2, characterized in that: The coal gangue aggregate also includes natural crushed stone, and the natural crushed stone accounts for 30% of the total amount of the coal gangue aggregate with a size of 0 to 5 mm.
4. The coal gangue filled roadbed water-stabilizing layer according to claim 1, characterized in that: The straw fiber is made of rice straw.
5. The gangue filled roadbed water-stabilizing layer according to claim 4, characterized in that: The rice straw has no rot or mildew on the surface and has good color.
6. The coal gangue filled roadbed water-stabilizing layer according to claim 4, characterized in that: The rice straw is soaked in a 5% by mass NaOH solution for 12 hours, and then washed and air-dried.
7. The gangue filled roadbed water-stabilizing layer according to claim 1, characterized in that: The content of the gelling material is 5.5%.
8. The gangue filled roadbed water-stabilizing layer according to claim 1, characterized in that: The mixing amount of the rice straw fiber is 3%.
9. The gangue filled roadbed water-stabilizing layer according to claim 8, characterized in that: The length of the rice straw fiber is 8 mm.
10. The method for constructing a water-stabilizing layer of a gangue-filled roadbed according to any one of claims 1 to 9, characterized in that: The following steps are involved: Construction preparation, preparation of construction raw materials and construction equipment; Raw material inspection: inspect the raw materials; Mix ratio selection; Mixing of mixed materials; The water content and cement dosage of the mixed material are tested. If the cement dosage test fails or the water content fails, the mixture mixing step is returned; Transportation of mixed materials: transporting the qualified mixed materials to the construction site and making test pieces; Use a paver to level and pave the ground, and keep the travel speed of the paver within 1.5m / min; Use a roller for static compaction, and control the roller's travel speed at 1.5-1.7 km / h; Elevation and flatness inspection. If the inspection fails, manual repair will be performed; The roller is used for shaping and vibrating. The speed of the roller is controlled at 1.8-2.5 km / h. The roller is rolled until there is no wheel mark. The roller overlaps 1 / 2 wheel width when rolling. Compactness test: if the test fails, the process returns to the roller forming and vibration step; Health preservation and finished product protection.
Citation Information
Cited By
Construction method for layered filling and particle size dynamic control of coal gangue roadbed
CN120158964A